TRAUMA AND SUBJECTIVE PRIMARY EXPERIENCE, ADAPTIVE LEARNING - Alpida Alpida; Puput Puput; Octavia Octavia; Rema Valencia; Elsa Magdalena; Aprianto Wirawan (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research aims to find out the extent of the role of parents, church psychiatrists or spiritual communities, friends or relations and even people who are very important in helping children in implementing appropriate or efficient learning strategies for children who experience this trauma. This research uses qualitative methods and interviews. In this study, researchers found responses from the interviewees when explaining the right learning strategies for traumatized children, the interviewees considered that the strategies that need to be done or pursued look at the age and education of children from the primary level, secondary level and even the upper level in approaching and making children aware of who is the focus of attention but not the center of attention that makes children able to tell what they are experiencing. Researchers conducted qualitative research by conducting interviews with Misiology students, International Reformed Evangelical College, housewives and teachers of SMK Negeri 2 Muara Teweh, IAKN Palangka Raya students.